Olympic Games Impact Study - Final report (2005)
In May 2004, the International Olympic Committee (IOC) placed London on the shortlist of candidate cities to host the Olympic and Paralympic Games ('the Olympics') in 2012. London subsequently provided further information about its bid in response to the IOC's request and, in July 2005, the IOC announced that London's bid had been successful.